(untitled) (International Journal of Physiotherapy, 2025)
Background: Stroke is a leading cause of long-term disability, impairing motor and functional capacities. Stroke rehabilitation focuses on regaining independence, yet the most effective interventions remain under study. This randomized controlled trial evaluated the efficacy of structured mirror therapy (MT) compared to general physiotherapy exercise over 24 weeks. Methods: A total of 100 stroke survivors were randomized into two groups: the MT group (n = 50) and the general physiotherapy exercises group (n = 50). The MT group received 5 times, 15-minute daily sessions for 21 consecutive days. The intervention was administered until the patient was discharged, and the patient was followed up in a community setting if their hospital stay was less than 21 days. Post-tests were conducted at discharge, with follow-ups via phone every 15 days and formal assessments at weeks 6, 12, and 24. Primary outcomes included the Barthel Index (BI) for functional independence and the Rivermead Motor Function Assessment (RMFA) for motor recovery of mobility. Results: Baseline characteristics were broadly similar, though the MT group had higher education, more skilled occupations, and more severe ischemic strokes. The MT group showed notably better improvements, with BI increasing from 13.02 to 27.78, compared to 15.10 to 22.82 in controls (P < 0.001), while RMFA improved from 43.54 to 76.00, compared to 49.44 to 70.08 (P < 0.001). Repeated-measures ANOVA confirmed significant group differences (BI: F = 84.759, P < 0.001; RMFA: F = 302.679, P < 0.001). Subgroup analyses revealed better outcomes with early MT initiation (within 7 days) in ischemic stroke cases. Conclusion: Structured MT significantly enhances motor and functional recovery post-stroke, independent of sociodemographic factors. Integrating MT into routine rehabilitation could improve recovery, reduce caregiver burden, and boost quality of life. Long-term studies are warranted.